ANALISIS PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI PT MY REPUBLIC JAKARTA - Purnama Putra, Bayu; Mursyidah, Azizah; Abrori; Adiputra, Nugroho; Zompi (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
This study aims to measure job satisfaction and employee performance at PT My Republic Jakarta and analyze the impact of job satisfaction on employee performance using a quantitative approach. Primary data was collected through questionnaires with 100 respondents, while secondary data was obtained from documentation, journals, and other sources. The research results indicate that job satisfaction has a significant positive impact on employee performance, with a regression coefficient of 0.303 and a significance level of < 0.05. This study used quantitative methods to gather primary data related to job satisfaction and employee performance. Additionally, secondary data was obtained from company archives provided by the director or owner, including the organizational structure, employee data, and job descriptions. The findings show that job satisfaction levels vary among employees and that job satisfaction positively influences employee performance.